2014
DOI: 10.1111/jch.12448
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory vs Office Blood Pressure Monitoring in Renal Transplant Recipients

Abstract: Hypertension is common following renal transplantation and has adverse effects on cardiovascular and graft health. Ambulatory blood pressure monitoring (ABPM) is better at overall blood pressure (BP) assessment and is necessary to diagnose nocturnal hypertension, which is also implicated in poor outcomes. The authors performed a retrospective analysis of 98 renal transplant recipients (RTRs) and compared office BP and ambulatory BP recordings. ABPM revealed discordance between office BP and ambulatory BP in 61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 23 publications
4
26
2
5
Order By: Relevance
“…Underestimation of BP control by office measurement was also found in a previous study, which showed 21% were hypertensive by ABPM but normotensive by office BP measurement. Even though our study did not reveal white coat hypertension, the previous studies demonstrated 3%‐10% of RT patients had white coat hypertension . Among patients with uncontrolled hypertension not detected by office BP measurement, 13.3% (2/15) had nighttime hypertension.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Underestimation of BP control by office measurement was also found in a previous study, which showed 21% were hypertensive by ABPM but normotensive by office BP measurement. Even though our study did not reveal white coat hypertension, the previous studies demonstrated 3%‐10% of RT patients had white coat hypertension . Among patients with uncontrolled hypertension not detected by office BP measurement, 13.3% (2/15) had nighttime hypertension.…”
Section: Discussioncontrasting
confidence: 82%
“…Among patients with uncontrolled hypertension not detected by office BP measurement, 13.3% (2/15) had nighttime hypertension. In a previous study in pediatric RT patients, 33%‐38% of nocturnal hypertension would be missed by office BP measurement and accentuated the importance of ABPM for the detection nocturnal hypertension …”
Section: Discussionmentioning
confidence: 99%
“…Posttransplant HTN is a multifactorial phenomenon and the known causes of HTN include immunosuppressive drugs, renal graft artery stenosis, recipient's native kidney, allograft dysfunction, obesity, recurrent or de novo renal disease, and genetic factors . However, optimal office and ambulatory BP targets have not been well‐defined in the renal transplant populatıon and there is variance depending on the cutoffs and series …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, 24 hr monitoring should be performed routinely [18,19] in this category of patients, due to involvement of immunosuppressant drugs and pro-inflammatory status in the development of arterial hypertension [20,21,22].…”
Section: Discussionmentioning
confidence: 99%